DIGITAL LIBRARY ACCEPTANCE ANALYSIS USING COMPUTER-ASSISTED QUALITATIVE DATA ANALYSIS SOFTWARE (CAQDAS) AT UIN SUNAN AMPEL SURABAYA - Rosyadi, Muhammad Zaidan; Rozas, Indri Sudanawati; Khalid, Khalid (Jurnal TAM (Technology Acceptance Model), 2023)
This study aims to determine the factors that influence the interest of UIN Sunan Ampel Surabaya students in using the Digital library. This study uses the Content Analysis model using the Computer-Assisted Qualitative Data Analysis Software (CAQDAS) technique as the sampling method. The number of samples in this study were 6 informants. Content Analysis according to Krippendorff, (2004) is a research method used to arrive at conclusions that can be replicated with valid results from the data to the context, with the result being new insights, representations of facts and practical guidance for action. To manage the data that has been obtained in the field, researchers use the NVivo software. The results obtained show seven significant conclusions, that the acceptance of the Digital Library by UIN Sunan Ampel Surabaya students is good enough with constructive answers.